Aridity decreases soil protistan network complexity and stability. (March 2022) - Chen, Qing-Lin; Hu, Hang-Wei; Sun, An-Qi; Zhu, Yong-Guan; He, Ji-Zheng
Abstract: Protists are ubiquitous and abundant in soil and contribute to key ecosystem processes including nutrient cycling and top-down regulation of soil microbiome. Drought stress will change the protistan community composition and network stability, which introduces uncertainty to predict their functions under a changing climate. A field survey was conducted across >2000 km in contrasting interior land and coastal areas of eastern Australia. We found aridity was the best predictor of protistan community composition, despite significant differences in soil physicochemical and biological properties between the two regions. Aridity may increase the importance of stochasticity in protistan community assembly, while decrease their community-level niche overlaps. More importantly, aridity may reduce the network complexity and stability, based on the difference in network topological features between inland and coastal sites. Altogether, our work provided new insights into the mechanisms through which aridity alters soil protistan communities and highlighted the importance of considering protistan networks when projecting ecological consequences under the climate change scenarios. Highlights: Aridity was the best predictor of protist community composition. Stochasticity played a more important role in protistan community assembly. Aridity expanded the protistan niche breadth but reduced the niche overlaps. A higher complexity and stability of protistan networks were identified in coastal regions.